The demography effect on Tri Kaya Parisudha based cognitive behavioral counseling effectiveness - Kadek Suranata (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2020)
This study aims to develop a cognitive-behavior counseling model based on Tri Kaya Parisudha in improving students' non-cognitive skills. Participants in this study were 45 students. The resilience data were obtain by Indonesian version of resilience scale and analyzed with ANOVA aided by the JASP program. The results of the study found that; (1) the cognitive-behavior counseling model based on Tri Hita Karana is effective in improving students' resilience (2) there is a difference in effectiveness model in overall area of students (3) programs that achieve acceptance and accessibility by students and the school counselor.